African Spiny Mice (Acomys) Exhibit Mild Osteoarthritis Following Meniscal Injury. (March 2023) - Chan, Kiara M.; Thurlow, Nat A.; Maden, Malcolm; Allen, Kyle D.
Objective: Hyaline cartilage has limited innate healing abilities and hyaline cartilage loss is a hallmark of osteoarthritis (OA). Animal models can provide important insights into cartilage regeneration potential. One such animal model, the African spiny mouse ( Acomys ), is capable of regenerating skin, skeletal muscle, and elastic cartilage. This study aims to evaluate whether these regenerative abilities protect Acomys with meniscal injury from OA-related joint damage and behaviors indicative of joint pain and dysfunction. Design: Acomys received destabilization of the medial meniscus (DMM) surgery ( n = 11) or a skin incision ( n = 10). Gait testing occurred at 4, 6, 8, 10, and 12 weeks after surgery. At endpoint, joints were processed for histology to assess cartilage damage. Results: Following joint injury, Acomys with DMM surgery altered their walking patterns by increasing the percent stance time on the contralateral limb relative to the operated limb, thereby reducing the amount of time the injured limb must bear weight on its own throughout the gait cycle. Histological grading indicated evidence of OA-related joint damage in Acomys with DMM surgery; these changes were primarily driven by loss of structural integrity in the hyaline cartilage. Conclusions: Acomys developed gait compensations, and the hyaline cartilage in Acomys is not fully protected from OA-related joint damage following meniscal injury, although this damage was less severe than that historically found in C57BL/6 mice with an identical injury. Thus, Acomys do not appear to be completely protected from OA-related changes, despite the ability to regenerate other wounded tissues.